2000
DOI: 10.1182/blood.v95.11.3489
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking flt3 ligand have deficient hematopoiesis affecting hematopoietic progenitor cells, dendritic cells, and natural killer cells

Abstract: The ligand for the receptor tyrosine kinase fms-like tyrosine kinase 3 (flt3), also referred to as fetal liver kinase-2 (flk-2), has an important role in hematopoiesis. The flt3 ligand (flt3L) is a growth factor for hematopoietic progenitors and induces hematopoietic progenitor and stem cell mobilization in vivo. In addition, when mice are treated with flt3L immature B cells, natural killer (NK) cells and dendritic cells (DC) are expanded in vivo. To further elucidate the role of flt3L in hematopoiesis, mice l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
278
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 772 publications
(292 citation statements)
references
References 44 publications
12
278
0
2
Order By: Relevance
“…Consistent with in vitro findings, Flt3L and its receptor Flt3, a member of the tyrosine-kinase receptor family, comprise the major extracellular signaling pathway regulating steady-state pDC and cDC generation from BM progenitors in vivo [13]. GM-CSF, on the other hand, is generally believed to be less relevant for steady-state DC development.…”
Section: Introductionsupporting
confidence: 52%
“…Consistent with in vitro findings, Flt3L and its receptor Flt3, a member of the tyrosine-kinase receptor family, comprise the major extracellular signaling pathway regulating steady-state pDC and cDC generation from BM progenitors in vivo [13]. GM-CSF, on the other hand, is generally believed to be less relevant for steady-state DC development.…”
Section: Introductionsupporting
confidence: 52%
“…FLT3 plays an important role in the control of haematopoiesis. In fact, studies of FLT3 Ligand (Fl )/) ) and FLT3 receptor (Flk2 )/) ) mice have demonstrated a key role of FLT3 signalling in early lymphopoiesis, with reduced numbers of progenitors of multiple lymphoid lineages, including lymphoid primed multipotent progenitors (LMPP), a progenitor common for the granulocyte-macrophage (GM) and lymphoid, but not megakaryocytic-erythroid lineage (Mackarehtschian et al, 1995;McKenna et al, 2000;Sitnicka et al, 2002Sitnicka et al, , 2007. Recent studies indicate that FLT3 is expressed and plays an important role in regulation of earliest stages of normal GM-progenitors development (Boiers et al, 2010).…”
mentioning
confidence: 99%
“…To date, long-term growth of pro-B cells required co-culture on stromal cells, yet the specific role of stromal cells in this culture system was unknown. Clearly IL-7, IL-7R (CD127), SCF and its receptor (CD117) as well as FLT3 and its receptor (CD135) all play a role in B-cell development and/or pro-B-cell growth [11,12,15,16,18,19]. Indeed, we now show that EPLMs efficiently grow and differentiate into pro-B cells when cultured in the combined presence of IL-7, SCF and FLT3L without contact with stromal cells.…”
Section: Discussionmentioning
confidence: 64%